Study of runaway electron behaviour during electron cyclotron resonance heating in the HL-2A Tokamak - 张轶泼 杨划蔚 刘仪 宋先瑛 袁国梁 李旭 周艳 周俊 杨青巍 陈燎原 饶军 段旭如 潘传红 HL-2A Team (Chinese physics B, 2009)
During the current flat-top phase of electron cyclotron resonance heating discharges in the HL-2A Tokamak, the behaviour of runaway electrons has been studied by means of hard x-ray detectors and neutron diagnostics. During electron cyclotron resonance heating, it can be found that both hard x-ray radiation intensity and neutron emission flux fall rapidly to a very low level, which suggests that runaway electrons have been suppressed by electron cyclotron resonance heating. From the set of discharges studied in the present experiments, it has also been observed that the efficiency of runaway suppression by electron cyclotron resonance heating was apparently affected by two factors： electroh cyclotron resonance heating power and duration. These results have been analysed by using a test particle model. The decrease of the toroidal electric field due to electron cyclotron resonance heating results in a rapid fall in the runaway electron energy that may lead to a suppression of runaway electrons. During electron cyclotron resonance heating with different powers and durations, the runaway electrons will experience different slowing down processes. These different decay processes are the major cause for influencing the efficiency of runaway suppression. This result is related to the safe operation of the Tokamak and may bring an effective control of runaway electrons.